Experiences of caregiving mothers of adolescents hospitalized for chronic diseases in a unit of adolescents (Research, Society and Development, 2020)
Objective: to describe the experiences of mothers who care for adolescents hospitalized for chronic illness. Methodology: Descriptive study with a qualitative approach, developed in a unit specialized in adolescent health at a large university hospital in the State of Rio de Janeiro, Brazil. Thirteen mothers caring for adolescents participated. Data collection took place during the months of April to June 2019, using the semi-structured interview technique. Results: it was revealed that the care performed by mothers, to a large extent, is lonely, with a high demand for time to be dedicated and knowledge, in addition to many economic difficulties. The feelings experienced and experienced by these women when they present themselves in a negative way, are manifested by insecurity, fear and anger. Conclusion: the report, from the set of experiences of mothers caregivers, reached in this study serves as subsidies for the development of new research on the theme, in addition to helping in the elaboration of diagnoses about the way of life of these women.